Institutional Quality and the Gains From Trade - Axel Borrmann; Matthias Busse; Silke Neuhaus (Hamburg Institute of International Economics (HWWA), 2006)
While theoretical models suggest that trade is likely to increase productivity and income levels, the empirical evidence is rather mixed. For some countries, trade has a strong impact on growth, whereas for other countries there is no or even a negative linkage. We examine one likely prerequisite for a welfare increasing impact of trade, that is, the role of institutional quality. Using several model specifications, including an instrumental variable approach, we identify those aspects of institutional quality that matter most for the positive linkage between trade and growth. We find that, above all, labour market regulation is the key to reducing trade-related adjustment costs. Market entry regulations, the efficiency of the tax system, the rule of law and government effectiveness do play a role too. In essence, the results demonstrate that countries with low-quality institutions are less likely to benefit from trade.
Keywords: P48; L51; F16; O17; 330; Trade; Income Levels; Institutional Quality; Regulations; Good Governance; Außenwirtschaft; Wirtschaftswachstum; Einkommenseffekt; Good Governance; Neue Institutionenökonomik